Developing a novel antibacterial dental resin composite with improved properties. (September 2019) - Wen, Xin; Almousa, Rashed; Anderson, Gregory G; Xie, Dong
A novel antibacterial resin composite has been developed and evaluated. Glycerol dimethacrylate was derivatized to have an antibacterial moiety attached and incorporated to a conventional resin composite formulation. Compressive strength and bacterial viability were used to evaluate the modified resin composites. Results showed that the modified resin composites showed a significantly enhanced antibacterial activity along with improved mechanical and physical properties. It was found that bromine-containing resin composite showed a higher antibacterial activity than its chlorine-containing counterpart. The modified resin composites showed an increase of 37–41% in yield strength, 23–27% in modulus, 9–15% in diametral tensile strength and 5–12% in flexural strength and a decrease of 35–69% in bacterial viability, 20–37% in water sorption, 7–12% in shrinkage and 7–10% in compressive strength, as compared to unmodified resin composite. Within the limitations of this study, the modified resin composite may potentially be developed into a clinically useful dental restorative since it demonstrated good mechanical strengths and potent antibacterial function.